Things, Assemblages, Worlds: Locating Vibrancy Beyond a Subject-Object Relationship (A Tale of Disposition) - Couillard, Paul (Imaginations)

(untitled) (York University, 2023)
"Things, Assemblages, Worlds" argues that the vibrancy of things is attributable not to an inherent quality within matter, but to the relationality of the perceptual field or world that things and bodies share. Reading Martin Heidegger's analytic of Dasein against Brian Massumi's description of things in their connectability allows for a revised description of how art sensitizes us to things through defamiliarization. Adina Bar-On's performance Disposition provides a useful example for uncovering art's ability to reveal things' character, their who-ness.